Mapas de zonas de risco de epidemias e zoneamento agroclimático para o Cancro Cítrico no Estado de São Paulo - Lopes, Mariana Vilela [UNESP]; Barreto, Modesto [UNESP]; Scaloppi, Érika Auxiliadora Giacheto; Barbosa, José Carlos [UNESP]; Brunini, Orivaldo (Grupo Paulista de Fitopatologia, 2008)
O cancro cítrico, causado pela bactéria Xanthomonas axonopodis pv. citri Valterin et alii 1995, é uma doença conhecida mundialmente e sempre constituiu séria ameaça para a citricultura brasileira. O objetivo do presente trabalho foi analisar as condições climáticas do Estado de São Paulo e desenvolver mapas de zonas de maior risco de epidemias de cancro cítrico. Foram utilizados dados meteorológicos referentes aos anos de 2002 a 2005, os quais foram baseados no modelo de previsão desenvolvido por Campbell & Madden (4) e Hau & Kranz (10). A freqüência dos dados foi horária e quando alguma estação apresentava falha, esses eram extrapolados da estação mais próxima. Foram contabilizados os índices de favorabilidade e posteriormente calculadas as porcentagens de dias favoráveis à ocorrência da doença no período de um ano. A partir destas informações, foram gerados os mapas temáticos do Estado de São Paulo, com a distribuição espacial da porcentagem de dias favoráveis à ocorrência de cancro cítrico. A região Noroeste do Estado foi a que apresentou a maior porcentagem de dias favoráveis à ocorrência de cancro cítrico.

The citrus canker, caused by the bacterium Xanthomonas axonopodis pv. citri Valterin et alii 1995, is a known disease world-wide known and it is always a serious threat for the brazilian citriculture. The objective of the present study was to analyze the climatic conditions of the State of São Paulo in order to develop zone maps of great risk for citrus canker epidemics. They had been used given meteorological referring from the years 2002 to 2005, which had been used in the model of forecast of citrus canker developed by Campbell and Madden in 1990 and Hau and Kranz in 1990. The data frequency was in hourly and when some metheorological station showed problems in the data series, these had been surpassed of the nearest station. After the accounting of the indexes had been calculated the percentages of days favorable to the occurrence of the disease in the period of one year. From this information, the thematic maps of the state of São Paulo had been generated, with the space distribution of the percentage of days favorable to the occurrence of citrus canker. The region the northwest region of the state was the one that presented the greatest percentage of days favorable to the occurrence of the disease.
Maps of zones of risk epidemics and agriculture climatical zoning of the citrus canker in the State of São Paulo
Keywords: Citros; Xanthomonas axonopodis pv. citri; geofitopatologia; Citrus; Xanthomonas axonopodis pv. citri; Geofithopathology